1987
DOI: 10.1038/bjc.1987.189
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cell inactivation by cis-dichlorodiammineplatinum in combination with 1-propargyl-5-chloropyrimidin-2-one

Abstract: Summary A synergistic effect with respect to inactivation of human NHIK 3025 cells cultured in vitro was displayed when treatment with cis-dichlorodiammineplatinum(II) (cis-DDP) and the mitotic inhibitor 1-propargyl-5-chloropyrimidin-2-one (NY 3170) were given in simultaneous combination. Cell inactivation was measured by loss of colony-forming ability. Treatment with NY 3170 alone produced no significant inactivation at concentrations up to 2mM. However, treatment with NY 3170 in combination with cis-DDP indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In order to be arrested in G2, damage to DNA alone is insufficient; there must also be replication of DNA on the damaged template -an effect which has also been observed in cells treated with alkylating agents (Roberts, 1978). It has been suggested that cells are more sensitive to cisplatin in GI (Roberts & Fraval, 1980) or at the GI/S boundary (Dornish et al, 1987) compared with S-phase. If the G2 block is a critical step in cell death, then our observation that cells treated in GI become blocked in G2 while those treated in S-phase move through G2 and divide is consistent with this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be arrested in G2, damage to DNA alone is insufficient; there must also be replication of DNA on the damaged template -an effect which has also been observed in cells treated with alkylating agents (Roberts, 1978). It has been suggested that cells are more sensitive to cisplatin in GI (Roberts & Fraval, 1980) or at the GI/S boundary (Dornish et al, 1987) compared with S-phase. If the G2 block is a critical step in cell death, then our observation that cells treated in GI become blocked in G2 while those treated in S-phase move through G2 and divide is consistent with this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a role of active transporters in the uptake and efflux of cisplatin and other platinum compounds has been available in the literature for some time . For example, multiple studies demonstrated that reactive aldehydes inhibit cisplatin accumulation in cells, possibly by modifying membrane proteins. , Recently, a series of experiments have indicated a direct link between copper transporters and the uptake and efflux of platinum compounds . The first clue came when cisplatin resistance was observed following transfection of a copper-transporting P-type ATPase (ATP7B), a key player in copper homeostasis, into human epidermoid carcinoma cells, which enhanced the efflux of the drug .…”
Section: 2 Facilitated Cellular Uptake and Efflux Of Platinum Complexesmentioning
confidence: 99%
“…In another group of experiments, this group has found that the mitotic inhibitor l-propargyl-5-chloropyrimidin-2-one (NY 3170) synergistically enhances DDP toxicity (Dornish et al, 1987 . In order to determine if the decreased uptake could be explained by a change in the plasma membrane, Mann et al.…”
mentioning
confidence: 99%